Impact of project crashing on construction cost / Nurulazmin Nadzari - Nadzari, Nurulazmin (2006)
Time and cost are the main factors in the construction industry. Projects that are not completed within the scheduled time will cause additional costs in many aspects. This study is conducted to identify and to analyze the impact of project crashing on construction cost for private and government projects around Pulau Pinang in year 2006. A ten (10) case study was selected randomly and one (1) case study had been shown detail analysis to crash the project duration and its impact on construction cost. It focuses on method to apply crash techniques, identify which activities are most applied the crash techniques, identify the impact on duration and cost, benefit of project crashing and the effect of project without applied the crash techniques. This research also determines how far we can crash the duration of the project. The data for this research were collected using interview with relevant people such as Project Manager. An effort has been made to add to the next with diagrams, tables and performance data, which together with the worked examples that enable the reader to prepare the project planning and cost estimation for the project crashing. This is to ensure timely and successful completion of projects to the satisfaction of all parties involved in the process. This study will benefit those are involved in construction, both building and civil engineering based on the cost control concept.